Which humanity would space colonization save?. (June 2019) - Traphagan, John W.
Highlights: Uniformity of human interests and desires is a fallacy. Is colonization of space important from the perspective of humans who are living in poverty?. Culture profoundly shapes the ways in which people think about their own interests and the interests of humanity. Abstract: Arguments in favor of space colonization often work from an intriguing pair of assumptions: 1) the interests of intellectual and political elites are equivalent to those of most or all of Earth's population, and 2) an (ethnocentric) Abrahamic view of the world that humanity is special and, thus, there is a moral requirement to preserve its creaactivities. In this article, I explore and unpack some of the problems with these assumptions in relation to the justification of space colonization. I do not take a position either for or against colonization; rather, I argue that we need to be careful in thinking through—deeply—what we mean when we talk about the interests of "humanity" and the moral necessity of preserving the species.